A clinical and radiological review of 204 hiatal hernia operations. Issue 3 (May 1973) - Hoffman, E.; Sumner, M. C.
Abstract : Two hundred and four patients with reflux oesophagitis and hiatal hernia were operated on by a modified Allison's technique and followed up for one to 10 years. To avoid surgical bias, the clinical and radiological findings were assessed by the co-author, a radiologist. Ages, type of hernia, symptoms, coexisting pathology, and operative technique are described. The late follow-up includes an assessment of patients' opinions of their operation and residual symptoms and a review of the radiological findings. The management of 25 patients with fibrous strictures is described. Factors preventing reflux are discussed. Current operative procedures for reflux oesophagitis are reviewed. In this series of 204 cases, five patients, that is 2·5%, were surgical failures. They were all dissatisfied with their operation and their symptoms had not improved; radiologically three of them showed reflux or an irreducible hiatal hernia. This failure rate is not considered unreasonable and the modified Allison's procedure is therefore recommended for patients with reflux oesophagitis.